Examination of the role and challenges of natural catalysts in hydrogen and biohydrogen production. Issue 3 (22nd March 2023) - Suyitno, Suyitno; Rosyadi, Imron; Caroko, Novi; Yusuf, Mirza; Adriyanto, Feri
Abstract: The high demand for hydrogen has led to the development of various production methods. This study examines the use of synthetic and natural catalysts in the generation of hydrogen and biohydrogen. A bibliographic analysis was conducted using the VOSviewer and ScientoPy tools. The research focuses on hydrogen synthesis, purification, separation, and storage, based on the findings. Hydrogen and biohydrogen can be produced through processes such as reforming, decomposition, hydrolysis, gasification, photolysis, and fermentation. The most studied approach is natural gas steam reforming, using Ni and Ce as catalysts and Al₂O₃, Al₂O₄, and BaTiO₃ as support materials, resulting in a high turnover frequency (TOF) of 2880 h −1 and an average stability of 100 h. In contrast, ammonia borane (AB) hydrolysis with Pt/Co₃O₄ catalysts may achieve a high TOF of 15 times faster than steam methane reforming (SMR). Additionally, HY‐zeolite containing nickel has a maximum stability of 578 h. Enhancing hydrogen and biohydrogen generation could be achieved by incorporating two or more metals that work synergistically and by building hierarchical structures in zeolite. In photocatalysis, it is important to design catalysts that improve light absorption. Using activated natural zeolites in the gasification process (conventional, supercritical, or hydrothermal) requires various raw materials and advanced chemical processes, which poses challenges for future work. Abstract : There any major changes in the processes undertaken for hydrogen and biohydrogen production. Synthetic and natural zeolites can enhance and boost the efficiency of the production of hydrogen and biohydrogen.